The effect of video-based multimedia training on knowledge, attitude, and performance in breast self-examination - Zahra Karimian; Roya Zare; Nahid Zarifsanaiey; Nasim Salehi (BMC, 2022)
Abstract Background/Objectives Breast neoplasm is one of the most common cancers in Iranian women due to the late diagnosis. Awareness of breast neoplasm and using Breast Self-Examination (BSE) assist in the early detection and treatment of cancer. This study examined the effectiveness of video-based multimedia training versus face-to-face training in awareness of breast neoplasm and BSE and possible factors affecting their effectiveness. Methods This research was a pre-test, a post-test experimental study comparing the knowledge, attitude, and performance of women about BSE across two training intervention groups (face-to-face versus video-based multimedia). The study was conducted at Shiraz University of Medical Sciences (SUMS), and 100 women between 20 to 60 years old were allocated to each intervention group via multi-stage cluster sampling (n:110). Three valid and reliable researcher-made questioners were used. Data were analyzed using SPSS 24 with independent t-test, paired t-test, and ANOVA. Results Both video-based multimedia and face-to-face training methods significantly increased the participant's knowledge, attitude, and skills about breast self-examination (P < 0.001). In the sub-categories, the results showed that the face-to-face training improved negligence and forgetfulness in applying BSE (P = 0.03) and correcting or modifying the previous knowledge around the issue (P = 0.02). The effect of the video-based method on participants with university education was more than on non-university (P = 0.04). Conclusion Incorporating video-based multimedia training in awareness of breast neoplasm and breast self-examination provides an easy, flexible, and affordable way for detection, particularly considering crisis restrictions. This can be of particular attention in more populated, developing/low-income countries and rural and remote areas to enhance equitable access to training and facilitation diagnosis and treatment if applicable.